HCI data-driven feedback in interactive learning environment - Chan, Matthias (2017)
Technological advancements have bridged the distance factor in learning communication (e.g. e-Learning platforms) by providing automated means for learners to access multimedia learning content. However, there still exists a gap in bridging the e-Learning to be as effective and sustainable as traditional learning due to the absence of the human factor, the teacher. Through the observing emotional changes, evaluating the probable cause for the change and adjusting feedback to remedy the situation, i.e. when to provide a feedback and the likelihood of acceptance by a learner, my proposed research aims to provide a dynamic and sustainable method of teaching and learning for effective learning intervention.